1970
DOI: 10.3329/jbcs.v24i2.9705
|View full text |Cite
|
Sign up to set email alerts
|

Determination of essential and toxic metals in meats, meat products and eggs by spectrophotometric method

Abstract: The concentration of essential metals such as Fe, Cu, Mg, Co and Zn and toxic metals such as Pb, Cd, Cr, As and Ni were determined in a number of animal meats, organ meats, meat products, and eggs by using UV-visible and atomic absorption spectrophotometry ( The concentration of arsenic in all samples was found negligible and this indicates that the investigated samples are safe from arsenic toxicity. The concentrations of other four toxic metals being very negligible in most of the samples indicate that these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
34
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 4 publications
10
34
15
Order By: Relevance
“…Demirulus argued that variation of Zn contents in yolk and albumen of eggs from villages and counties can be because of geographical and dietary differences and environmental pollution. Table 1 indicates that the mean concentration of Mg is less than that of egg-white reported by other works by Forson et al (2011) and Chowdhury et al (2011). Another important mineral for body health is magnesium.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…Demirulus argued that variation of Zn contents in yolk and albumen of eggs from villages and counties can be because of geographical and dietary differences and environmental pollution. Table 1 indicates that the mean concentration of Mg is less than that of egg-white reported by other works by Forson et al (2011) and Chowdhury et al (2011). Another important mineral for body health is magnesium.…”
Section: Resultscontrasting
confidence: 62%
“…The results of this paper are lower than those reported by Abduljaleel et al (2011) and Siddiqui et al (2012) who found Fe level ranged from 78.5 ± 14.6 mg/kg and 12.2790 mg/kg, respectively. Chowdhury et al (2011) indicated that Fe content in white and yolk of eggs in Chittagong city, Bangladesh, was 9.48 ± 0.005 mg/kg, 115.1 ± 0.003 mg/kg, respectively; iron content in egg samples from Nigeria and the UK varies between 21.80 and 24.10 (Leblanc et al, 2005) and 20 mg/kg (Azza & Hanaa, 2011). Mean level of Zn in a sample is 0.066 mg/kg (from 0.0025 to 0.475 mg/kg; Table 1).…”
Section: Resultsmentioning
confidence: 97%
“…It was observed that the levels of zinc and chromium (dry and fresh weights, fw) in this study were much higher than those reported by others, a further indication of substantial contamination of the Nigerian environment by zinc and chromium. [32][33][34][35] Most zinc enters the environment as the result of mining, zinc purification, lead and cadmium ores, steel production, coal burning, and waste burning. Chromium sources may come from waste effluents discharged from textile, pigment, leather tanning, and electroplating industries, and/or incineration of municipal refuse and sewage sludge.…”
Section: Discussionmentioning
confidence: 99%
“…The residual concentrations of heavy metals in cow blood could be an important "direct indicator" of the safety status of cow meat consumed, as well as an "indirect indicator" of the degree of pollution of the environment in which the cow was breed. One of the main problems with metals is their ability to bio-accumulate in plant (Bhatti et al, 2016) and animals (Akbar- Jan et al, 2011;Chowdhury et al, 2011;Lotfy et al, 2013;Abd El-Salam et al, 2013;Li et al, 2015;Ogamba et al, 2016).…”
Section: Introductionmentioning
confidence: 99%